Analysis and Comparison of Mangrove Forest Area on the South Coast of East Java Using the 2 Canal Algorithm of Landsat-8 Satellite Image. - Hafidh Shalahuddin Arsyadhani; Siti Zainab (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
Trenggalek and Malang districts are among the coastal cities in East Java that have mangrove forests. The function of mangroves as a wear prevention to maintain the plains is the background of this research. The purpose of this study is to compare the vegetation density of mangrove forests in Trenggalek and Malang using Landsat 8 image 2 channel algorithm method by calculating the vegetation index value with NDVI and EVI methods. The difference in vegetation values can be seen based on thematic maps with differences in average diameter of mangrove trees where in mangrove forests in Trenggalek Regency has an average diameter of mangrove trees of 6.55 cm while in Malang Regency has an average diameter of mangrove trees of 5.73 cm. There are also differences in vegetation values based on the two methods used in the study, namely NDVI and EVI show differences in vegetation values. Using the NDVI method, the vegetation value is 0.53232 for the Malang area while 0.6263 for the Trenggalek area. Although both are classified as very dense, there is a difference in the t-test on the average vegetation value using the NDVI method. Using the EVI method, the vegetation value of 0.33994 for the poor area is classified as moderate while 0.42033 in the Trenggalek area is classified as dense.